Love Me Little, Love Me Long - Reade, Charles, 1814-1884 (Salt Lake City, UT : Project Gutenberg, 2003)
"Love Me Little, Love Me Long" by Charles Reade is a novel written during the mid-19th century. The story primarily revolves around Lucy Fountain, a young lady navigating her social relationships and the expectations placed upon her due to familial obligations and societal norms. The narrative begins with Lucy being placed under the care of her two trustees after the death of her mother, leading to interactions that explore themes of love, ambition, and personal freedom. The opening of the novel introduces Lucy as she adjusts to living with her Aunt Bazalgette. The characters engage in witty conversations, revealing their personalities and the tensions within their lives. Lucy's relationship with her cousin Reginald is characterized by playful banter, while her aunt expresses frustration with societal expectations, particularly in the context of marriage and appearances. As Lucy transitions between living with her various guardians, the groundwork is set for her internal conflict regarding love and autonomy, suggesting that her journey will delve deeper into the complexities of relationships and self-identity. (This is an automatically generated summary.)
Sequel: Hard Cash.
Release date is 2003-11-01
Produced by James Rusk and David Widger
Keywords: England -- Social life and customs -- 19th century -- Fiction; Mate selection -- Fiction; Courtship -- Fiction